2017
DOI: 10.1136/bmjspcare-2017-001351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a patient-tailored complementary/integrative medicine programme on disturbed sleep quality among patients undergoing chemotherapy

Abstract: NCT01860365.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…The lack of a significantly greater improvement in overall QoL in the intervention arm contrasts with prior pragmatic trials which showed significantly greater improvement on EORTC‐reported functioning and symptom severity scales (e.g., anxiety, insomnia) with IO therapies 27,28 . The equivocal outcomes for QOL‐related outcomes in the present study may have resulted from the use of a protocolized CIPN‐directed CIM interventions, which focused more on relief of CIPN and less on general and holistic (e.g., overall well‐being) outcomes.…”
Section: Discussioncontrasting
confidence: 86%
“…The lack of a significantly greater improvement in overall QoL in the intervention arm contrasts with prior pragmatic trials which showed significantly greater improvement on EORTC‐reported functioning and symptom severity scales (e.g., anxiety, insomnia) with IO therapies 27,28 . The equivocal outcomes for QOL‐related outcomes in the present study may have resulted from the use of a protocolized CIPN‐directed CIM interventions, which focused more on relief of CIPN and less on general and holistic (e.g., overall well‐being) outcomes.…”
Section: Discussioncontrasting
confidence: 86%
“…Pragmatic research has shown that patient-tailored IO treatments have a positive impact on sleep quality, depression and anxiety in patients with breast and gynecological cancer undergoing chemotherapy. 17,18 While patient-tailored IO programs may generate non-specific effects, there is still a need to explore specific emotional-related effects, particularly anxiety and depression during chemotherapy. 19 The present study focused on a specific patient population undergoing adjuvant or neo-adjuvant chemotherapy for localized cancer.…”
mentioning
confidence: 99%
“…Many studies have discussed which factors promote quality of life among cancer survivors, increasingly investigated since the publication of the EORTC multicentre study [48]. The authors proposed physical activity, yoga sessions, psychological management, or treatments such as melatonin for insomnia [37,[49][50][51]. Opinions concerning the role of alternative medicine remain controversial.…”
Section: Discussionmentioning
confidence: 99%